Impact of the French Revolution and the Napoleon Wars on Industry Mobility, The Military and The Economy in England Country - Gusriandari, Wahyu; Pertiwi, Ayu; Saputro, Guntur Eko (Journal of Social Work and Science Education, 2023)
The subject matter occurred at the start of the French Revolution and Napoleonic Wars which caused various problems such as poverty caused by damage to the industry through various continental blockades which triggered an increase in prices resulting in an economic crisis and had an impact on increasing government spending on war costs. The purpose of this study is to find out how the impact of the French Revolution and Napoleonic wars on the industrial, military, and economic mobility of the British state which focuses on the struggle for power aimed at conquering it. Thus, researchers use quantitative methods that use literature studies by collecting various data and information which are then processed to produce precise and accurate conclusions according to the facts that have occurred or will occur. This war has a long-term impact that builds inhibits the development of the world economy. The results of the war research have destroyed economic resources, agriculture and factories were all abandoned due to the war which resulted in people not having enough money to buy basic necessities and having to defend themselves. The strategy of the UK was to continue to borrow heavily for its war expenditure at relatively low rates. However, Britain's tax rate did not change much as long as it earned a peacetime surplus that offset the wartime deficit and paid off the mounting war debt.